'The new attractive mine': 36 research areas for attractive workplaces in future deep metal mining. (29th December 2014) - Johansson, Bo; Johansson, Jan
Future efficient mining operations will be dependent upon a highly competent and well motivated work force, on all levels. The mining companies will have to recruit their personnel from a limited group of talented individuals with high demands and expectations on future work. In order to be successful with this, the companies must offer attractive workplaces that are safe, sound, interesting and can offer challenging work tasks too. In this paper we discuss a number of potential challenges for the future mining industry based on the fact that the majority of the mines are expected to be deeper and located in remote areas. Our intention is to illustrate a possible way forward for the mining industry. We start by describing a vision for such a safe and attractive mine. After that we present a comprehensive and possible research agenda necessary for creating the 'New Attractive Mine'.